2022
DOI: 10.1186/s12935-022-02704-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the modified systemic inflammation score in non-small-cell lung cancer with brain metastasis

Abstract: Background Brain metastases (BM) from non-small-cell lung cancer (NSCLC) is the most common brain malignancy. Systemic inflammation biomarkers have recently been evaluated as prognosis indicators in several tumors. The combination of these markers has not been evaluated in NSCLC with BM yet. Here, we explored the predictive value of pretreatment inflammatory biomarkers and established a novel, clinically applicable prognostic index for NSCLC patients with BM. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Diving deeper into the prognostic potential of immune parameters, several groups uncovered that the neutrophil-lymphocyte ratio (NLR) and serum albumin levels served as independent harbingers of enhanced survival in NSCLC patients with brain metastasis [139]. When NLR and albumin metrics were integrated to conceive the modified systemic inflammation score (mSIS), it outperformed the discriminative capability of the AJCC's seventh T + N staging system [140]. In parallel, another research contingent identified the prognostic relevance of the prognostic nutritional index (PNI) and systemic immune inflammation index (SII) for NSCLC patients manifesting brain metastases [141].…”
Section: Immune Cells and Serological Biomarkersmentioning
confidence: 99%
“…Diving deeper into the prognostic potential of immune parameters, several groups uncovered that the neutrophil-lymphocyte ratio (NLR) and serum albumin levels served as independent harbingers of enhanced survival in NSCLC patients with brain metastasis [139]. When NLR and albumin metrics were integrated to conceive the modified systemic inflammation score (mSIS), it outperformed the discriminative capability of the AJCC's seventh T + N staging system [140]. In parallel, another research contingent identified the prognostic relevance of the prognostic nutritional index (PNI) and systemic immune inflammation index (SII) for NSCLC patients manifesting brain metastases [141].…”
Section: Immune Cells and Serological Biomarkersmentioning
confidence: 99%
“…Already early on in the pandemic and long before vaccines were available, it became clear that patients with a diagnosis of cancer are at significantly higher risk of becoming infected with SARS-CoV-2 [1]. In an analysis of electronic health record (EHR) data from the USA, patients with active cancer (diagnosis of cancer within the last year) were found to be even more receptive to an infection than the overall population of patients with a diagnosis of cancer [1].…”
Section: Introductionmentioning
confidence: 99%
“…Already early on in the pandemic and long before vaccines were available, it became clear that patients with a diagnosis of cancer are at significantly higher risk of becoming infected with SARS-CoV-2 [1]. In an analysis of electronic health record (EHR) data from the USA, patients with active cancer (diagnosis of cancer within the last year) were found to be even more receptive to an infection than the overall population of patients with a diagnosis of cancer [1]. In fact, adjusted odds of an infection (adjustment for gender, age, race, coronavirus disease 2019 risk factors, cancer treatments, transplantation, stay in a nursing home) were higher for patients with non-Hodgkin lymphoma, lung cancer, breast cancer, colorectal cancer, and prostate cancer, while patients with leukemia (adjusted odds ratio [aOR] 12.16) appeared to be at the highest risk of an infection compared to patients without cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations